Study of causal aeroallergens in allergic rhinitis - Aggarwal, Divya; S., Abhilash; Kapur, Sunil; Gupta, Divya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The diagnosis of allergic rhinitis requires a detailed history, thorough clinical examination and identification of aeroallergens by skin prick test. The diagnosis cannot be confirmed on the basis of symptoms alone because both allergic and non-allergic rhinitis can present with similar symptoms. The present study was undertaken to identify the common aeroallergens causing allergic rhinitis and to find any relationship of the severity of patient’s symptoms with raised levels of absolute eosinophil count, percentage of eosinophils in the peripheral blood and total serum IgE. Methods: It is cross sectional study was conducted among 100 patients including both the genders attending out-patient department of ENT. The patients were divided into mild, moderate and severe disease categories based on nasal symptom score (NSS) which was calculated taking into account the severity of four symptoms namely sneezing, watery rhinorrhoea, itching sensation in nose and nasal obstruction. Results: 76% of patients had moderate nasal symptom score and 42% had symptoms of allergic rhinitis for less than 3 years. The prevalence of skin prick test was strongly positive for pollens (46.19%), followed by dust (16.4%), dust mites (15.7%), fungus (9.7%), insects (9.24%) and epithelia (2.77%). But, among 68 aeroallergens, most common offending allergen was D-farinae (30%). There was no significant relationship found to exist between Eosinophilia, Absolute eosinophil count and serum IgE level with that of nasal symptom score. Conclusions: Skin prick test is the gold standard investigation of choice for definitive diagnosis of allergic rhinitis.